2017
DOI: 10.1080/19382014.2017.1404211
|View full text |Cite
|
Sign up to set email alerts
|

The adverse effects of chronic low-dose exposure to nonylphenol on type 2 diabetes mellitus in high sucrose-high fat diet-treated rats

Abstract: Chronic low-dose exposure to NP might induce impaired glucose tolerance, which further lead to insulin resistance, and pancreatic β cell insulin secretion deficiency, ultimately increase the risk of T2DM. Moreover, additive toxic effects of NP and HSHFD on pancreatic beta-cell function and glucose metabolism have been identified in rats as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…The results of animal experiments in this study showed that the body weight of rats increased during 1 to 17 weeks of NP exposure, while the weight of rats increased significantly from 21 to 26 weeks and presented a positive relationship with NP dose. NP-induced weight gain in rats has also been demonstrated in multiple studies [25,28,29]. In this study, the serum cholesterol, triglyceride, and low-density lipoprotein contents of the rats in the exposed group were higher than these in the control group, which was consistent with the results of Zhang et al [30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of animal experiments in this study showed that the body weight of rats increased during 1 to 17 weeks of NP exposure, while the weight of rats increased significantly from 21 to 26 weeks and presented a positive relationship with NP dose. NP-induced weight gain in rats has also been demonstrated in multiple studies [25,28,29]. In this study, the serum cholesterol, triglyceride, and low-density lipoprotein contents of the rats in the exposed group were higher than these in the control group, which was consistent with the results of Zhang et al [30].…”
Section: Discussionsupporting
confidence: 91%
“…These studies were consistent with these in vitro results, which suggested that NP exposure had an effect on adipocyte lipid metabolism. The results of the above cell experiments and animal experiments have confirmed our previous research findings that NP exposure could cause 2-diabetes [28], alcoholic fatty liver [29], and metabolic syndrome [27].…”
Section: Discussionsupporting
confidence: 87%
“…Low-dose effects were defined by the National Toxicology Program (NTP) as those that occur in the range of human exposures or effects observed at doses below those used for traditional toxicological studies (Vandenberg et al, 2012). Actually, there is growing evidence to support low-dose effects of NP (Melnick et a., 2002; Di et al, 2018; Patino-Garcia et al, 2018; Yu et al, 2018). Nonmonotonic dose-response curves, a nonlinear relationship between dose and effect where the slope of the curve changes sign somewhere within the range of doses examined, is best explanation for the low-dose (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a large number of human studies and experimental animal models demonstrated that adverse environmental exposures experienced by their parents during intrauterine or early postnatal life significantly influenced health of the next generations (Dong et al, 2019; Lund et al, 2019; Zhang et al, 2019). More specifically, poor early-life exposures robustly increased the risks of developing chronic metabolic diseases in adult life, including glucose intolerance, T2DM and obesity (Csongova et al, 2018; Kearney et al, 2018; Wen et al, 2018; Yu et al, 2018; Chang et al, 2019). This association has been conceptualized by the fetal programming hypothesis and the developmental origins of health and disease, which propose that environmental stimuli during critical windows of development programmed permanent changes in later life (Aris et al, 2018; Velazquez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%